The Images of Illegal Economical Activities and the Fight against Them in Lithuanian Press in 1938–1940 - Indrišionis, Darius (Lietuvos istorijos studijos, 2020)
Various illegal economical activities such as speculation, moonshine production, etc. were popular subjects in the Lithuanian press of 1938–1940. Economic problems were important for the Lithuanian society during those harsh years, so these publications did their part to influence public opinion. This article focuses on the most popular narratives of illegal economical activities in the Lithuanian press of 1938–1940: 1) the Price Control Officer and his struggle against speculation; 2) propaganda methods in solving the problem of moonshine (illegal breweries); 3) other illegal economical activities (illegal medical or law practice, prostitution, etc.). In conclusion, Lithuanian authorities used mild methods against the illegal part of the economy. The Price Control Officer, one of the most popular authority figures in 1938–1940 Lithuania, used to bribe businessmen who were mixed up in speculation and to publish lists of those so called “speculators” periodically. This policy was morally doubtful because it influenced some antisemitic thoughts (as the majority of those bribed “speculators” were of Jewish descent). Police methods were not enough to reach victory against widespread moonshiners. In the summer of 1938, a high-scale propaganda campaign against moonshine was launched. Fighting other illegal economical activities was problematic due to a lack of jurisprudence and legal alternatives.
Keywords: interwar Lithuania; price control officer; speculation; moonshine; illegal economical activities; prostitution; propaganda